Pendidikan Berbasis Muatan Lokal Sebagai Sub Komponen Kurikulum - Marliana, Marliana; Hikmah, Noor (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2013)
The introduction of the state of the environment, society, and culture to students enabling them to more to their environment. The introduction and development of the environment through education geared to support the quality of human resources, and ultimately directed to improve the ability of learners. School as a place of education program, a part of the community. Therefore, education programs in schools need to provide extensive knowledge about the specificity of the learners in their environment. Subjects should be made based on local content prepared by the school environment that is tailored to each area. The function of the existence of local content is to broaden the knowledge of students in accordance with the condition of the area. Local content is one of the means for students to develop the knowledge, skills and potential of art owned by the school and the area in which the school is located. Application of local curriculum between one region to another is different. To realize local content -based education at a school needs support with all relevant stakeholders and continuously evaluates to develop the potential of the region. It is not impossible a local charge when packaged in a professional manner will carry the name of the region to national and even international level. Required more in-depth study and togetherness between schools, communities, local governments for the successful implementation of the local content -based education.